Design and development real-time multi-point temperature sensing system based on microcontroller - Zheng, Shuangyue (2016)
Leakage on the pipe is a problem in natural gas transmission system. The tem- perature at leakage point drops due to Joule-Thomson effect. The material of gas pipe was iron which has a good conductivity led to temperature dropping to 1 to 2 cm far away from the leakage point. Instead of traditional way to monitor the temperature change by thermocouple, digital temperature sensor DS18B20 was used to check the its performance and help to collect temperature information when the leakage occurred on the pipe. The collected results shows that the size of the leakage affected the temperature dropping at the center of the leakage point and the range. By comparing the experimental results and simulations results, it shows that the experimental setup was not as expected.